The Permanent Income Hypothesis: Estimation and Testing by Instrumental Variables - Hayashi, Fumio (Journal of Political Economy, 1982)
The permanent income hypothesis with rational expectation is restated, estimated, and tested by an instrumental variables technique on the postwar U.S. aggregate time-series data. The hypothesis is accepted on a consumption series which includes service flows from consumer durables. If the consumption series is the one in the National Income and Product Accounts, the hypothesis is decisively rejected. An explanation is suggested to reconcile the conflicting test results.